Subtropical carbonates from the Callovian Calabozo Formation, and their diagenesis, Neuquen Basin, Mendoza province - Palma, R.M. (2007)
Detailed study of Callovian carbonates of the Calabozo Formation (30 m) in western Argentina, reveals the abundance of benthic carbonates particles produced by organisms that are light dependent, and non-skeletal grains such as ooids and peloids. The biota consists of bivalves, dasyclads (Salpingoporella annulata Carozzi, Cylindroporella annulata Carozzi, and Heteroporella sp.), scleractinian corals, echinoderms, cyanobacteria (Cayeuxia (Rivularia) piae Rech-Frollo, and Cayeuxia (Rivularia) kurdistanensis Elliot), oncoids, gastropods, forams, and calcispheres as well as ostracods, and bryozoans in relatively minor quantities. Allochemical particles suggest for the shallow marine limestones of the Calabozo Formation a Photozoan Association under subtropical seawater conditions. The petrographic features allow to recognize seven microfacies, differentiated by particle types, fossils and depositional texture: 1) criptalgal bindstone; 2) bioclastic-peloidal wackestone; 3) bioclastic-intraclastic wackestone; 4) bioclastic-peloidal-terrigenous wackestone, 5) coral framestone, 6) peloidal-bioclastic-intraclastic packstone, and 7) oolitic-bioclastic-peloidal packstone-grainstone. The recognition of microfacies groups constitute two palaeoenvironmental associations: inner ramp and middle ramp settings. Diagenetic studies are based on examination of stained thin sections, through conventional petrography and under cathodoluminescence. Early diagenetic processes are micritization and precipitation of peloidal micrite and acicular calcite. These cements predate granular and syntaxial calcite cements. Cathodoluminescent petrography allows to identify three morphologic types of clear cements: (1) fine acicular crystals, (2) granular cements, and (3) syntaxial cement rims on echinoderm particles. Description of the CL signature has evolved to discrimination as either, non-luminescent, dully luminescent red/orange, or brightly luminescent yellow. The earlier acicular calcite cement is non-luminescent, on the other hand, the predominantly dully luminescent red/orange, or brightly luminescent yellow of interparticular and intraparticular granular calcite and syntaxial cements indicate a shallow burial meteoric-phreatic diagenetic environment.